Luteolin reduces necroptosis in the diabetic heart after cardiac arrest and resuscitation by activating sirtuin 3 - Yang, Jin-Ting; Jiang, Chun-Yan; Zhang, Zi-Yan; Tang, Li-Hui; Lou, Yang-Yun; Qian, Ling-Bo (Frontiers in Nutrition, 2025)
BackgroundsMyocardial impairment resulting from cardiopulmonary resuscitation (CPR) contributes to the elevated mortality in diabetes. Luteolin, a naturally occurring polyphenolic compound abundant in vegetables, fruits, and nuts, has been shown to mitigate myocardial I/R injury in diabetes by suppressing oxidative stress. However, whether luteolin confers cardioprotection following cardiac arrest (CA) and CPR in diabetes remains unclear. Sirtuin 3 (Sirt3), a mitochondrial deacetylase, has been reported to attenuate diabetic cardiomyopathy by reducing oxidative stress and inflammation-mediated necroptosis. Recent evidence suggests that luteolin can upregulate Sirt3 and enhance mitochondrial function. Thus, we hypothesized that luteolin may alleviate post-CA/CPR myocardial injury in diabetes by inhibiting necroptosis through activation of the Sirt3 signaling pathway.MethodsDiabetes was induced in male Sprague-Dawley rats via a single intraperitoneal injection of streptozotocin (65 mg/kg). Rats were then treated with luteolin (100 mg/kg, i.g.) or Sirt3 inhibitor 3-TYP for 2 weeks. Subsequently, diabetic rats were subjected to 5 min of asphyxia-induced CA followed by CPR. After 6 h of resuscitation, left ventricular function, myocardial infarction, oxidative stress markers, inflammatory cytokine release, mitochondrial function, necroptosis-associated protein expression, and both Sirt3 expression and enzymatic activity were assessed.ResultsLuteolin significantly improved post-resuscitation cardiac function and reduced myocardial infarction, oxidative stress, and pro-inflammatory cytokine levels in diabetic rats. It also inhibited cytosolic Ca2+ overload, mitochondrial permeability transition pore opening, and loss of mitochondrial membrane potential. Additionally, luteolin activated Sirt3 and superoxide dismutase 2. Importantly, luteolin increased the expression of Sirt3 and suppressed necroptosis by down-regulating phosphorylated receptor-interacting protein kinase 3 and phosphorylated mixed lineage kinase domain-like protein. The cardioprotective effects of luteolin were abrogated by co-administration of 3-TYP, indicating a critical role for Sirt3 in mediating these benefits.ConclusionLuteolin protects diabetic hearts after CA/CPR by suppressing necroptosis, primarily through activation of Sirt3, which dampens oxidative stress and inflammation, and maintains mitochondrial integrity.